EFFECTS OF PLANNING ON PERFORMANCE OF COUNTY GOVERNMENTS IN KENYA - Wahinya, Grace Njeri (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to determine the effect of planning on performance of county governments in Kenya. Questionnaire was used to collect data from seven counties in Kenya drawn from 47 county governments in Kenya.Two tools of analysis were adopted by this study namely: correlation analysisand regression analysis. The correlation analysis was used to show the positive correlation between the predictorand response variables while regression analysis was used to explain the relationship between the predictor and response variables. R-squared was used to provide the strength of the relationship between the model and the response variable and determine its goodness fit. While F statistics was used to test the significance of the regression model. The study adopted correlational research design. The findings revealed that performance of county government is significantly influenced by planning. From the findings, the study concludes that the county governments should enhance on further improvement in the area of planning in order to enhance the benefit of planning on performance of county governance. Key Words: Planning,Performance, County Government,